Optimization Of RNA Extraction And Generation Of Expressed Sequence Tags From Sargassum Binderi (Sonder) J. Agardh - Wong, Tony Kok Min (2005)
Brown seaweeds are macroalgae in the marine habitat. They are widely used as food, sources for cosmetics, pharmaceuticals, soap, agar, textile, and alginate. Sargassum binderi is one of the most abundant brown seaweeds in Malaysia. Previous studies have shown that S. binderi contains high quality of alginate compared to commercially used seaweeds such as Laminaria hyberborea, Macrocystis pyrifera and Ascophyllum nodosum. Expressed sequence tag (EST) approach is a powerful tool in providing genetic information of an organism, especially for S. benderi in which little genetic information is available. This study presents the first attempt in generating ESTs from S. binden. RNA extraction from seaweeds was the main challenge in this study, as the RNA yield was low and the polysaccharide contamination was difficult to be eliminated. A total of ten different RNA extraction methods (including five modifications) have been carried out to obtain sufficient RNA of high quality to construct a representative cDNA library for ESTs generation. The optimized S. binderispecific CTAB RNA extraction method developed in this study was able to produce high yield of RNA with minimum polysaccharide contamination. Sufficient amount of mRNA was obtained to construct a primary cDNA library with a titer of 9.2 x lo5 pfulml. A total of 2051 ESTs were generated and analyzed from the amplified cDNA library of S. binden (with a titer of 1.31 x lo9 pfulml). The ESTs were putatively identified by comparison to the nonredundant peptide database in NCBI. Approximately 82% of the ESTs were assigned as unknown and novel sequences that are potentially important for new gene discovery, whereas the 18% ESTs with significant matches to the database were classified into various putative functional groups, including protein synthesis, energy, protein destination and storage, metabolism, cell structurel division, diseasel defense, signal transduction, transcription, and miscellaneous. The EST information generated from this study may contribute towards better understanding of the biochemistry and molecular biology of S. binder; and other brown seaweeds in the future.